Analysis of Learning Difficulties in Mathematics Regarding 3d Geometric Shapes Materials at SDN 2 Weru - Nuha, Auliyatun; Subayani, Nataria Wahyuning (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to determine the difficulties of learning cubes and rectangular prisms experienced by 5th grade students. The research method used was quantitative descriptive methods with a sample of 18 students and the 5th grade teachers at SD Negeri 2 Weru. Data collection techniques were carried out by observation and interviews. The results of the research show that: a) Students' ability to draw cubes and rectangular prisms is in the high category with a percentage of 83.33%. This can be seen in the suitability of student work results with the instructions given; b) Students' ability to identify geometric elements in images is in the very low category, with a percentage of 33.33%; c) Students' ability to determine the volume and surface area of a cube is in the moderate category with a percentage of 61.11%; d) Students' ability to determine the volume and surface area of a rectangular prism is in the low category with a percentage of 55.55%; and e) Students' ability to determine the volume and surface area of a rectangular prism based on the image presented is in the very low category with a percentage of 38.89%. Difficulties in learning mathematics faced by students include the inability to distinguish between cubes and rectangular prisms and their elements, difficulty while answering questions and applying formulas, the basics of multiplication are not yet strong, and lack of motivation to learn.